Deiksis dalam Film “Ku Kira kau Rumah” : Analisis Pragmatik - Rizka Ardillah Ardillah; Kingkin Puput Kinanti; Luly Zahrotul Lutfiyah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
This research is a discussion of pragmatic studies, namely deixis. deixis itself is a word that has no reference depending on what, who, where and when the speech occurs. The purpose of this research is 1) to explain the forms of deixis, 2) to explain the meaning of deixis, 3) to explain the function of deixis. the research data is in the form of the movie "Ku Kira Kau Rumah" by using qualitative description research method that describes in detail the observed case. The result of the research is there are 5 forms of deixis which are 1) persona deixis, 2) place deixis, 3) time deixis, 4) discourse deixis, 5) social deixis and each deixis has its meaning and purpose.